Enteric pathogens in HIV/ AIDS from a tertiary care hospital - Uppal Beena; Kashyap Bineeta; Bhalla Preena (Wolters Kluwer Medknow Publications, 2009)
Background: Patterns of enteric infections in HIV in developing countries may differ in several important ways from developed countries, the knowledge of which can often guide therapy when resource limitations hamper the exact diagnosis of the etiological agent in HIV-associated diarrhea. Objectives: The primary objective of this study was to define and compare the microbial etiologies of diarrhea in HIV-1 infected and non infected patients and in HIV infected non diarrheal patients. Materials and Methods: This study was conducted between April 2007 and July 2007 at the Department of Microbiology, Maulana Azad Medical College, New Delhi. Stool samples from 50 HIV seropositive cases with diarrhea (study group), 50 HIV seropositive cases without diarrhea (control group I), and 50 HIV seronegative cases with diarrhea (control group II) were examined. After the diagnosis of HIV infection was made, routine parasitological and bacteriological detection was done. An ELISA was used for the detection of Clostridium difficile toxin and Cryptosporidium antigen in stool samples. Results: The overall prevalence of enteric parasitosis in the study group was 20% and the bacteria identified were Escherischia coli in 24% of the case, Clostridium difficile in 10% of the cases, Salmonella species and Vibrio cholerae in 4% of the cases, and Shigella species in 2% of the cases. Candida species was identified in 36% of the cases. Conclusions: Identification of the etiological agent of diarrhea in a patient with AIDS is very important as it can help in the institution of appropriate therapy and the reduction of morbidity and mortality in these patients.